Adaptive Reuse through Layering: Transforming the Rex Trueform Clothing Factory - Mundey, R L (School of Architecture, Planning and Geomatics, 2014)
The announcement in March 2005 of the imminent closure of the Rex Trueformclothing manufacturing plant in Salt River created a large impact on the CapeTown economy in view of the nearly 1000 jobs that were at risk. The reason forthe closure, according to management, was due to globalisation.1Four years have past since the last garment was produced in this factorybuilding, which was designed in 1934 by one of Cape Town's best-knownmodernist architects, Max Policansky. It is now abandoned and derelict -left fordead with the possibility of demolition threatening its existence.This thesis will focus on the adaptive reuse of the Rex Trueform ClothingFactory in Salt River. I am proposing to transform the Rex Trueform Factory intoa Skills Training- & Workshop Facility for the Cape Town Garment Industry. Thisnew facility will provide learning spaces for the training of those working in thegarment and textile industry, as well as offer a creative workshop environmentfor small clothing manufacturing enterprises. In addition, residential and retailspaces will be provided, as well as a clothing market.This project will also demonstrate how the layering of architectural modes ofexpression can produce delightful and surprising results. As cities constantlyevolve through dramatic change brought by large-scale new-built redevelopments,less obvious change occur as existing buildings undergo a morestable, continual mode of change and adaptation. Through this process,individual buildings can express the passage of time.